Analisis Keharmonisan Rumah Tangga Istri Berprofesi sebagai Ojek Online: Perspektif Teori Batas atau Hudud - M. Muslih; Moh. Dimyati (Bulletin of Community Engagement, 2024)
This research aims; 1) To find out the role of the wife who works as an online motorcycle taxi on household harmony in Langkapura Baru District, Bandar Lampung City, and 2) To find out the role of the wife who works as an online motorcycle taxi on household harmony from the perspective of boundary ir hudud theory in Langkapura Baru District, Bandar Lampung City. This research is field research carried out in Langkapura Baru District, Bandar Lampung. To obtain the necessary data, researchers used several techniques including observation, interviews and documentation. From the data obtained, both field data and library data are then collected and processed so that a conclusion can be drawn. Based on the research conducted by the researcher, it can be concluded that even though he is busy with work as a driver, the wife does not abandon her obligations as a wife and mother. Communication with husband and children is maintained between family members. This is their effort to maintain household harmony. According to researchers, the wife, who works as an online motorcycle taxi driver in Langkapura Baru District, Bandar Lampung City, is related to the hudud theory proposed by Muhammad Syahrur because the wife can maintain the honor of herself, her husband and her family.